KUALITAS KIMIA SUSU KAMBING PERANAKAN ETAWA PADA BERBAGAI PERIODE LAKTASI DI DESA SUNGAI LANGKA KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Naldo Zaidemarno; Ali Husni; Sulastri . (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This research was conducted from May up to June, 2016 at Ettawa grade goat (EGG) development area, Sungai Langka village, Gedong Tataan subdistrict, Pesawaran regency to study chemical quality of EGG milk. Survey method were used in this research. Fifteen tails of EGG at first, second, third, and fourth lactation period as sample research was decided by purposive sampling procedure. Variables observed were fat, protein, solid non fat, and water content. Chemical quality of milk were analysed at Technology of Agriculture Product Laboratory, Politeknik Negeri Lampung (Polinela), Bandarlampung. Chemical quality of the milk was compared  Indonesia National Standard or Standar Nasional Indonesia (SNI) No 01-3141-1998 and Thai Agricultural Standard (TAS) 606-2008. Result of research indicated that fat content of 76.61 % samples (range of fat content 2.52 – 6.20 %) was qualified (standard of SNI was 3,7 %, TAS was 4.0 %). Protein content all samples (range 3.86 – 6.70 %) was qualified (standard of SNI was 2,7 %, TAS was 3.7 %). Solid non fat content all samples (range 9.54 – 11.92%) was qualified (standard of SNI was 8.0 %, TAS was 8.25).  Water content all samples (range 76.28 – 82.48 %) was qualified (standard maximum of SNI was 89 %, standard maximum of TAS was 87 %).It could be concluded that chemical quality of EGG milk was qualified to standard of SNI No 01-3141-1998 and Thai Agricultural Standard (TAS) 606-2008.  Key words: Ettawa Grade Goat, Fat Content, Protein Content, Solid Non Fat Content, Water Content